Evaluation of procalcitonin as a diagnostic marker in neonatal sepsis - Marie Victor Pravin Charles; Ramakrishnan Kalaivani; Soma Venkatesh; Arunava Kali; Kunigal Srinivasiah Seetha (Wolters Kluwer Medknow Publications, 2018)
Context: Neonatal sepsis is an early infection occurring within 28 days of the postnatal life. It has nonspecific signs and symptoms which make the diagnosis cumbersome. It inflicts an increase in morbidity and mortality among neonates. Procalcitonin (PCT) is yet another acute phase reactant, which is synthesized by the C-cells of thyroid gland. Aims: The aim of our study is to evaluate PCT as a diagnostic marker of neonatal sepsis in comparison with C-reactive protein (CRP). Subjects and Methods: A prospective cross-sectional study was conducted at our tertiary care hospital in Puducherry. The study was conducted over a period of 5 months from November 2015 to 2016. The study included all neonates with clinical signs of sepsis. The neonates were assigned into three groups as proven sepsis, suspected sepsis, and no sepsis group. The CRP level and PCT level were compared between the three groups, and their sensitivity and specificity were calculated. Statistical Analysis Used: The mean, standard deviation, and standard error of mean were calculated. The groups were compared using one-way ANOVA. The diagnostic test efficiency was evaluated by receiver operating characteristic curve analysis. Results: A total of 75 neonates were included in our study. There were 9 (12%) neonates with proven clinical sepsis, 47 (62.6%) neonates with suspected clinical sepsis, and 19 (25.3%) neonates with no sepsis. The mean and standard error of mean were calculated for CRP and PCT in all the three groups. The results showed a sensitivity of 88.90% for both CRP and PCT and specificity of 89.40% for CRP and 80.30% for PCT. The common organisms isolated from culture-positive group were Escherichia coli (22.2%), Pseudomonas aeruginosa (22.2%), and Candida albicans (22.2%), followed by Klebsiella pneumoniae, Acinetobacter baumannii, and methicillin-resistant Staphylococcus aureus. Conclusions: PCT may not be sufficiently used as a sole marker of sepsis in neonates compared to CRP. PCT in conjunction with CRP and other tests for septic screen can aid in better diagnosis of neonatal sepsis.